Analisis Faktor Kepuasan Dan Loyalitas Konsumen Terhadap Produk Espresso Based Coffee Di Filosofi Kopi Jakarta - Gara Dhita, Sylvia; Mukson, Mukson; Setiadi, Agus (Forum Agribisnis, 2025)
Espresso based coffee has an important role in the coffee shop industry, because it served as the base for a variety of popular coffee drinks, so it would be a popular choice for consumers to enjoy while relaxing or simply spending time. Filosofi Kopi, located in several strategic areas in Jakarta, offers many kinds of popular espresso based coffee products to consumers. Unfortunately, Filosofi Kopi has not implemented a suitable marketing strategy for its business operations. This is an important thing for business owners to analyze what consumers need as target market. Therefore, marketing mix 9P analysis must be done in order to evaluate consumer satisfaction, which has an impact on consumer loyalty of competing with competitors. The purpose of this research is to analyze the level of Filosofi Kopi customer satisfaction and loyalty by using the marketing mix 9P strategy. Satisfaction and loyalty levels of consumers have been analyzed by the Customer Satisfaction Index (CSI), Importance Performance Analysis (IPA), and customer loyalty pyramid methods. The research results showed that the CSI value was 83.97%, indicating that consumers are very satisfied with all the marketing mix 9P attributes in Filosofi Kopi. Based on IPA analysis using the cartesius diagram, performance and importance attributes in each quadrant should be maintained. The customer loyalty pyramid showed that espresso–based coffee consumers in Filosofi Kopi were in the “committed buyer” category with the highest percentage values of 80.71%. Consumer Satisfaction variable (Y) has dominant influence to Consumer Loyalty (Z). Through this research, it has been concluded and suggested to Filosofi Kopi that uses the marketing mix 9P to maximize “price” and “process” aspects to improve consumer satisfaction and loyalty, which has a positive impact.